Co3O4-chitosan/biomass-derived porous carbon molecularly imprinted polymer integrated electrode for selective detection of glucose. Issue 16 (15th August 2022) - Peng, Canwei; Miao, Longfei; Qiu, Dan; Chen, Shouhui
Abstract: The detection of glucose (Glu) is of great significance in medical diagnosis, food processing and biotechnology. Rapid, accurate and convenient detection technology is particularly important. Herein, the Co3 O4 -PC nanocomposite grown on biomass-derived porous carbon (PC) was prepared by hydrothermal method and subsequent air calcination. Chitosan (CS) was electrodeposited on the surface of Co3 O4 -PC by potentiostatic deposition with Glu as the template molecule. Finally, the template molecule was eluted by cyclic voltammetry to create specific recognition sites for Glu, and a highly selective and stable Glu sensor was constructed. The obtained MIP (molecularly imprinted polymer)-Glu-CS/Co3 O4 /PC nanocomposites were characterized by scanning electron microscopy, Raman spectroscopy, cyclic voltammetry, chronoamperometry and so on. The results showed that the MIP-Glu-CS/Co3 O4 -PC had great catalytic performance for Glu detection with a linear range of 12.17 μM-2.3 mM, a detection limit of 4.01 μM, and a sensitivity of 407.5 μA cm −2  mM −1 . The sensor has excellent selectivity and stability. This work provides a guide for improving the selectivity of nanozymes.